[Sea Cliffs] - Streng, Evelyn Fiedler (1975)
Photograph of a sea cliff. Brown, jagged rock formations form a cliff along the grey water to the left. White waves of the water rush on a dark, rock covered beach to the left. Grey clouds cover the sky at the top of the photograph.